Questions of modernity - Mitchell, Timothy, 1955- (Contradictions of modernity, 2000)
Modernity has always laid claim to universal certainty--which meant assigning a different and lesser significance to anything deemed purely local, non-Western, or lacking a universal expression. Focusing on the making of modernity outside the West, eight leading anthropologists, historians, and political theorists explore the production of new forms of politics, sensibility, temporality, and selfhood in locations ranging from nineteenth-century Bengal to contemporary Morocco.